Early versus delayed interventions for necrotizing pancreatitis: A systematic review and meta‐analysis. Issue 1 (10th October 2022) - Nakai, Yousuke; Shiomi, Hideyuki; Hamada, Tsuyoshi; Ota, Shogo; Takenaka, Mamoru; Iwashita, Takuji; Sato, Tatsuya; Saito, Tomotaka; Masuda, Atsuhiro; Matsubara, Saburo; Iwata, Keisuke; Mukai, Tsuyoshi; et al.
Abstract: Objectives: Interventions for necrotizing pancreatitis are generally postponed until 4 weeks after the onset of acute pancreatitis, but there remains controversy about whether we should always wait >4 weeks or can intervene early when necessary. This meta‐analysis was conducted to evaluate treatment outcomes of necrotizing pancreatitis according to the cut‐off defined in the revised Atlanta classification (≤4 vs. >4 weeks). Methods: Using PubMed, Web of Science, and the Cochrane database, we identified clinical studies published until March 2022 with data comparing outcomes of early and delayed interventions of necrotizing pancreatitis. We pooled data on adverse events, mortality, technical and clinical success rates, and needs for necrosectomy and open surgery, using the random‐effects model. Results: We identified 11 retrospective studies, including 775 patients with early interventions and 725 patients with delayed interventions. Patients with early interventions tended to be complicated by organ failure. The rate of adverse events was comparable (OR 1.41, 95% CI 0.66–3.01; p  = 0.38) but the rate of mortality was significantly higher (OR 1.70, 95% CI 1.21–2.40; p  < 0.01) in early interventions. Technical success rates were similarly high but clinical success rates tended to be low (OR 0.39, 95% CI 0.15–1.00; p  = 0.05) in early interventions, though not statistically significant. Pooled ORs for necrosectomy and open surgery were 2.14 and 1.23, respectively. Conclusions: Early interventions for necrotizing pancreatitis were associated with higher mortality rates and did not reduce adverse events or improve clinical success. However, our results should be confirmed in prospective studies.